The Impact of Religion on the ASEAN Community Education Strategy - Chen, Yixuan; Yang, Suping (Journal of Educational Research and Policies, 2026)
The ASEAN Community Education Strategy, as a crucial mechanism for promoting regional integration in Southeast Asia, has been profoundly influenced by religious factors in multiple dimensions throughout its formation and development. Based on policy text analysis and comparative research, this study systematically examines how major religions—primarily Buddhism and Islam—shape the ASEAN education strategy across six dimensions: educational goal-setting, content infiltration, resource allocation, regional coordination, modernization processes, and transnational cooperation. While religion performs positive functions through value internalization and resource integration, it also generates structural tensions due to doctrinal differences and traditional inertia. At the goal level, religion has shaped an educational orientation centered on spiritual cultivation and moral education. At the content level, religious curricula and interdisciplinary penetration have formed a distinctive knowledge system. At the resource level, religious institutions have compensated for the inadequacy of public education provision, but have also led to imbalanced allocation. At the coordination level, religious diversity has enriched cultural capital while increasing the difficulty of policy integration. At the modernization level, deep-seated conflicts exist between traditional religious education and modern educational concepts in terms of goals, methods, and curriculum design. At the cooperation level, religious networks provide unique channels for cross-border educational exchange. ASEAN needs to construct a positive interaction mechanism between religion and education under the framework of the “ASEAN Way,” advancing educational modernization while respecting cultural pluralism, in order to achieve the strategic goal of regional educational integration.